The effect of approach velocity on pelvis and kick leg angular momentum conversion strategies during football instep kicking - Augustus, S.; Hudson, P. E.; Smith, N. (Journal of Sports Sciences, 2021)
During football instep kicking, whole-body deceleration during the final stride has been associated with greater kick leg angular momentum and enhanced foot and ball velocities, but the influence of approach velocity on these mechanisms is unknown. This study assessed how approach velocity affects momentum conversion strategies of experienced players performing fast and accurate kicks. Eleven semi-professional footballers performed instep kicks from self-selected (3.34 ± 0.43 m/s), fast (3.71 ± 0.33 m/s) and slow (2.77 ± 0.32 m/s) approaches. Kicking motions and ground reaction forces under the support leg were captured using 3D motion analysis (1000 Hz). The players responded to perturbations in approach velocity by using the support leg to regulate whole-body deceleration and create ideal conditions for co-ordinated pelvic and kick leg momentums during the downswing. Further, the pelvis was key for generating transverse momentum at the kick leg, but the participants displayed distinctly different pelvis transverse rotation strategies. Identification of these inter-individual strategies may provide a basis for technical and strength training practices to be tailored for individual players. Future research might investigate if training practices that expose footballers to varying approach velocities of between 2.5 and 4.0 m/s promotes development of movement strategies that are robust to perturbations in approach conditions.